(3QMdI GdTGaYjs - (3CHh HcQ eMeO Hf EHQGgje Hf GdefPQ GdfjSGHhQj,J (B319 (3g` s ((3eMeO Hf CMeO Hf eMeO GdCUHgGfj s)
(3ChdgG (B:s
(3CNHQfG GdTjN GdEeGe YdGeI YdGAGdOjf CHhGdMSf Ydj Hf EHQGgje GHf OGhO GdTGaYj GHf GdYWGQ s
(3BNQgG (B:s
(3aMed Edi efRdg hde jRd ajg YdjdG MJi eGJ aj GdJGQjN GdePchQ QVj Gddg Yfg hCQVGAg s
(3HBNQ GdCUd Gdefbhd efg SeGY eDQN SfI (B584(3g`s
(3hgfGc SeGY BNQ aj ReGf GdfGSN JGQjNI SfI (B630(3g`s
(3hgh GdEeGe eMeO Hf EOQjS GdeJhaj SfI (B204 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B191 s
Keywords: (3GdJGQjNs